Factors Influencing Employee Engagement and its Impact on Organizational Performance - Prajapati, Nabin (Bagiswori Journal, 2022)
Purpose: The purpose of this study is to identify the factors affecting the employee engagement as well as to examine the effect of employee engagement on organizational performance. Design/Methodology/Approach: Descriptive and Analytical research design was used for data analysis. A convenient sample of 200 employees of Nepal Telecom responded to a structured questionnaire. Correlation and Regression analysis were performed to examine the hypothesis. Findings: The result shows that identified factors like career development, compensation, work environment, team and co-worker relationship, organizational policies and workplace wellbeing have positive and significant impact on employee engagement whereas Leadership has negative and insignificant impact on employee engagement. Further, the result also shows employee engagement had significant impact on organizational performance. Practical Implication: Organization must focus and effort on the factors like organizational policies and team and co-worker relationship as they have shown significantly higher impact on employee engagement and organizational performance. Organization should develop favourable organizational policies and focus on developing a good environment and promote such programmes that enhances team and peer relationship. Originality/Value: Managers must apply various strategies to make their employee engaged which is less prioritized till today.